Sustainable production of rare oleanane-type ginsenoside Ro with an artificial glycosylation pathway in Saccharomyces cerevisiae. Issue 21 (7th October 2022) - Ren, Shichao; Sun, Qiuyan; Zhang, Liang; Sun, Wentao; Li, Yongxing; Feng, Xudong; Li, Chun
Abstract : S. cerevisiae was genetically reprogrammed to produce ginsenoside Ro with seven exogenous enzymes from five species. This study also paved a good way for the synthesis of other complex glycosides of triterpenoids. Abstract : Ginsenoside Ro (Ro), the only identified oleanane-type pentacyclic ginsenoside, has the ability to provide antitumor, anticoagulant and other functions and has the potential to be applied in pharmaceuticals and tonics. Currently, Ro is mainly derived by direct extraction from ginseng; however, this method is not sustainable and cannot meet the increasing demand due to its low content and long culture period. In this study, we selected 29 enzymes from 15 different species to screen for key enzymes for Ro synthesis. Through both in vitro and in vivo characterization, seven enzymes from five species with high catalytic efficiency and substrate specificity were selected to construct an artificial dual glycosylation pathway for the de novo biosynthesis of Ro in Saccharomyces cerevisiae . The main route of Ro synthesis was identified through the in vitro enzymatic kinetics. Several metabolic engineering strategies were employed to strengthen Ro synthesis. Finally, the Ro titer reached 528.0 ± 18.0 mg L −1 in 5 L fed-batch fermentation, which was more than 374 000-fold higher than the reported data.